Hubungan Antara Kondisi Rumah Dengan Kejadian Tuberkulosis Paru Di Puskesmas Kismantoro Kabupaten Wonogiri - Ambar Sari, Dian (2016)
Tuberculosis is a public health problem in the world. Condition of the house plays an important role in the transmission of tuberculosis. This study aimed to analyze the relationship between the condition of the house with the incidence of pulmonary tuberculosis in Puskesmas Kismantoro, Wonogiri. This research is a quantitative research design Case Control. The population in this study are patients with smear-positive pulmonary tuberculosis in Puskesmas Kismantoro as many as 41 respondents and a sampling technique by calculating the minimum sample size and obtained a minimum sample of 40 respondents. The results showed that the area of home ventilation case group (82.9%) did not qualify and the control group (57.3%) qualified, home lighting in the case group (75.6%) and the control group (53.7%) did not qualify , moisture house case group (78.0%) and the control group (53.7%) did not qualify, the type of flooring the case group (56.1%) and the control group (65.9%) did not qualify, and type of ceilings case group (85.4%) and the control group (65.9%) are not eligible. Based on the results obtained by Chi Square test showed no relationship between ventilation (p = 0.001), home lighting (p = 0.038), humidity (p = 0.020),type of ceiling (p = 0.040) and there was no relationship between type of floor with the incidence of Pulmonary Tuberculosis.